A fluorometer-based method for monitoring oxidation of redox-sensitive GFP (roGFP) during development and extended dark stress - Rosenwasser, Shilo; Rot, Ilona; Meyer, Andreas; Feldman, Lewis; Jiang, Keni; Friedman, Haya (Physiologia plantarum, 2010)
Redox-sensitive GFP (roGFP) localized to different compartments has been shown to be suitable for determination of redox potentials in plants via imaging. Long-term measurements bring out the need for analyzing a large number of samples which are averaged over a large population of cells. Because this goal is too tedious to be achieved by confocal imaging, we have examined the possibility of using a fluorometer to monitor changes in roGFP localized to different subcellular compartments during development and dark-induced senescence. The degree of oxidations determined by a fluorometer for different probes was similar to values obtained by confocal image analysis. Comparison of young and old leaves indicated that in younger cells higher levels of H2O2 were required to achieve full roGFP oxidation, a parameter which is necessary for calculation of the degree of oxidation of the probe and the actual redox potential. Therefore, it is necessary to carefully determine the H2O2 concentration required to achieve full oxidation of the probe. In addition, there is an increase in autofluorescence during development and extended dark stress, which might interfere with the ability to detect changes in oxidation-reduction dependent fluorescence of roGFP. Nevertheless, it was possible to determine the full dynamic range between the oxidized and the reduced forms of the different probes in the various organelles until the third day of darkness and during plant development, thereby enabling further analysis of probe oxidation. Hence, fluorometer measurements of roGFP can be used for extended measurements enabling the processing of multiple samples. It is envisaged that this technology may be applicable to the analysis of redox changes in response to other stresses or to various mutants.
Gesehen am 21.06.2023